Challenging Obstetrical Management in Generalized Peritonitis during Pregnancy. (21st April 2022) - Oliveira, Susana Patrícia Lima; Sousa, Ana Isabel; Martins, Nuno Nogueira
Abstract : Acute abdomen in pregnancy represents a diagnostic and therapeutic challenge, despite the current advances in modern medicine, since the typical symptoms and altered laboratory parameters mimic normal pregnancy. Acute appendicitis is the most common nonobstetric surgical emergency during pregnancy, with an incidence of 1 per 500-2000 pregnancies. Delayed diagnosis and reluctance to operate on a pregnant woman predispose to adverse maternal and fetal outcomes. The elective termination of pregnancy or interventions to prolong it in the presence of appendicitis is controversial. We present a case of a 38-year-old Caucasian woman, G2P0, admitted to the Obstetric Emergency Department at 13 4/7 weeks of gestation with a primary complaint of severe nausea and vomiting associated with progressive diffuse abdominal pain which had started 7 days before. After the difficulty of inherent differential diagnosis, she was diagnosed with generalized peritonitis due to acute perforated appendicitis. Prompt exploratory laparotomy with appendectomy and drainage of multiple abscesses were performed. Conservative obstetrical management was assumed, with subsequent periodic monitoring of the fetal focus. Due to abdominal compartment syndrome, the abdomen was left open for 4 days. After 7 days in the intensive care unit, recovery was favorable, pregnancy remained uneventful, and a healthy full-term baby was born 27 weeks later. This case represents a successful example of how the cooperation of the obstetrics and general surgery teams and the decision of conservative obstetrical management in the surgical environment contributed to optimizing maternal health, achieving the best obstetrical outcome.